The breathing space clinic: a pilot to support the holistic needs of patients with advanced COPD. Issue 2 (1st September 2011) - Hodson, Matthew; Jennings, Rebecca; Martin, Jonathan
Abstract : The Breathing Space Clinic: a multi-disciplinary, inter-organisational hospice-based pilot clinic to support the holistic needs of patients with advanced chronic obstructive pulmonary disease (COPD). Introduction: In contrast to many other conditions, mortality trends indicate that the prevalence of COPD is increasing. Studies show that COPD patients' symptoms are at least as severe as those of patients with lung cancer and that this group is underserved by specialist palliative care. There are currently no reliable means of identifying when COPD patients enter their last year of life. Breathing Space combines the specialist expertise of both COPD-specific and palliative care teams to provide information, non-pharmacological and pharmacological interventions, advance care planning etc. The clinic thus aims to maximise quality of life for patients with very severe disease in response to need rather than prognosis. Aims: This presentation will outline the development and function of the Breathing Space Clinic, focusing on the rationale for our referral criteria and pathway. Methods: Clinic development involved collaboration between the hospice, COPD patients, primary care teams and specialist respiratory teams across three London boroughs. It targets those patients with very severe COPD who have complex needs, including those arising from co-morbidities. Referral criteria are designed to reflect this approach and are grounded in an alternative model to that of palliative care provision for cancer patients. The referral pathway is designed to ensure NICE compliance. Relevant metrics are collected. Results: Our presentation will include reflection upon early data from the pilot. Discussion: Significant time and multi-disciplinary effort was required to develop the clinic concept to an operational level. Challenges were encountered in developing explicit referral criteria and these will be reviewed in light of the clinic metrics. Conclusion: Collaborative interventions have potential to greatly improve patient care but require commitment and learning from all involved.